2017
DOI: 10.1089/dna.2017.3904
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of miR-629 Inhibits Ovarian Cancer Malignant Behaviors by Targeting Testis-Specific Y-Like Protein 5

Abstract: Ovarian cancer (OC) is the most lethal gynecological cancer. The molecular mechanism of it is complicated, and numerous researches suggest that microRNAs are key regulators for it. This study was to investigate the pivotal role of miR-629 in the progression of OC and to reveal the possible molecular mechanism of its action. Testis-specific Y-like protein 5 (TSPYL5) is a tumor suppressor gene in various cancers, but there is little for its role in OC. OC OVCAR3 cells were transfected with the miR-629 vector, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 25 publications
4
18
0
Order By: Relevance
“…In our results, we showed that miR‐629 was up‐regulated in hypoxia‐induced HPASMCs. Previous studies also showed the up‐regulation of miR‐629 in several types of cancers, and overexpression of miR‐629 showed enhanced effects on the cancer cells including cervical cancer, colorectal cancer, breast cancer and ovarian cancer . Consistently, our data showed that overexpression of miR‐629 promoted cell proliferation and inhibited cell apoptosis of HPASMCs, while knockdown of miR‐629 exerted the opposite effects in HPASMCs during hypoxia.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In our results, we showed that miR‐629 was up‐regulated in hypoxia‐induced HPASMCs. Previous studies also showed the up‐regulation of miR‐629 in several types of cancers, and overexpression of miR‐629 showed enhanced effects on the cancer cells including cervical cancer, colorectal cancer, breast cancer and ovarian cancer . Consistently, our data showed that overexpression of miR‐629 promoted cell proliferation and inhibited cell apoptosis of HPASMCs, while knockdown of miR‐629 exerted the opposite effects in HPASMCs during hypoxia.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, down‐regulation of miR‐126 contributed to the right ventricle failure in PAH and restoration miR‐129 expression in the right ventricle improved micro‐vessel density and right ventricle function in experimental PAH . miR‐629 was a newly identified miRNA and plays an oncogenic role in several types of cancers including cervical cancer, colorectal cancer, breast cancer and ovarian cancer . Despite the role of miR‐629 in cancer, the role of miR‐629 in PAH has not been investigated so far.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we found that miR-629-5p was up-regulated both in colorectal cancer tissues and cell lines. However, its extent of up-regulation in colorectal cancer is significantly lower than that in other cancer types [ 12 , 24 ], indicating a potential varied regulation of miR-629-5p in different types of cancer. Additionally, there was no significant correlation between the metastasis of tested cell lines and the expression level of miR-629-5p .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, another research highlighted TSPYL5 as a tumor inhibitor gene and was poorly expressed in PCa [17]. Similarly, previous research has demonstrated that decreasing TSPYL5 expression may influence ovarian cancer cell invasion and proliferation in a suppressive way [33].…”
Section: Discussionmentioning
confidence: 88%